Public library staff experiences of accommodation in the workplace - Hill, Heather (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2021)
<span data-sheets-value="{"1":2,"2":"Identifying as having a disability in the workplace can be a complicated proposition. This research examines public library staff experiences of accommodation for a disability within the workplace. Semi-structured interviews were conducted with Canadian public library staff who sought accommodation in their workplace. "}" data-sheets-userformat="{"2":8961,"3":{"1":0},"11":0,"12":0,"16":12}">Identifying as having a disability in the workplace can be a complicated proposition. This research examines public library staff experiences of accommodation for a disability within the workplace. Semi-structured interviews were conducted with Canadian public library staff who sought accommodation in their workplace.